Nostalgic Fanworks. Explanation of the Demake Category - Ziółkowski, Jakub (Replay. The Polish Journal of Game Studies, 2023)
The purpose of this article was to describe the category of demake in detail, which is a popular form of artistic expression among video game fans. This was achieved through an analysis of grow journalism focusing on the selected issue and two groups on the Reddit platform that bring together people interested in creating and playing demakes. At the beginning of the text there is an introduction of the reader to the discourse and a presentation of the methodology. Essential terms in this work were demake itself, remake, retrogaming, nostalgia, fan practices and corporate image-making of technology. These aspects helped to understand the demake and develop a relevant theory. The broad view of the category is an attempt to reconcile the knowledge gained by other researchers with the practices, habits and language of gamers, which often deviate from the academic order.